METHODS AND SKILLS FOR SPORTS DEVELOPMENT IN UZBEKISTAN - Tabynbaev Askar (Proximus Journal Publishing, 2024)
The article attempts to show the development of sports in recent years in Uzbekistan. It is noted that the priority direction of state policy is the formation of a physically and morally strong person, for whose development favorable conditions have been created
Keywords: Healthy generation; equipment and re-equipment; achievements in sports